Separation of acoustic multipaths in Saanich Inlet - DiIorio, D.; Farmer, D.M. (Canadian Acoustics, 1992)
Acoustical scintillation measurements can provide a basis for determining the properties of ocean structure in coastal waters and can be used as a tool to remotely measure oceanographic processes (e.g. current and turbulent structure) which differ markedly from processes in the open ocean. A scintillation experiment in 1989 was carried out in a coastal environment in British Columbia, Canada in order to relate acoustic characteristics to the oceanography. The experimental site was Saanich Inlet which is a deep (220 m), quiescent (maximum currents 10 cm.s-1) and stratified fjord. The goal is to compare acoustic propagation through this relatively undisturbed, coastal environment with previous measurements in a turbulent tidal channel